Cardiovascular Response to Verbal Communication a Study in Business Process Outsourcing Employees - Divya, P.; Veena, K. N. (International journal of physiotherapy, 2015)
Background: Cardiovascular changes to daily activity and stressors have been proposed as a mechanism for promoting the progression of atherosclerosis and coronary heart diseases. Hence, purpose of the study with objective is to assess the cardiovascular parameters such as heart rate, blood pressure and rating of perceived exertion responses to verbal communication in Business process outsourcing (BPO) employees. Method: A cross sectional survey design, selected 150 healthy subjects between age group of 25 to 35 years from BPO industry, Bangalore. Subjects who fulfilled inclusion criteria were included into the study. Heart rate and blood pressure were recorded before and after shift. The Borg rating of perceived exertion scale was also administered to find the difference of amount of exertion, which was felt by subjects before and after shift. Results: The analysis of measured variable shown that before shift the means Heart rate was 81.76 beats, the mean systolic blood pressure is 117.82 the mean diastolic blood pressure is 80.69 and the mean rate of perceive d exertion is 7.19. After shift the means of Heart rate was 83.02 beats, the mean systolic blood pressure is 120.32 the mean diastolic blood pressure is 83.26 and the mean rate of perceive d exertion is 10.65. When analysed using paired t test there is a statistically significant difference in before and after shift means of heart rate, blood pressure and rate of perceived exertion. Conclusion: It was concluded that in BPO employees in response to their verbal communication there was significant increase in cardiovascular responses including Heart Rate, Systolic Blood Pressure and Diastolic Blood Pressure. There was also a significant increase in Borg rating of perceived exertion before and after shift